Release Kinetics of Lawsone from the Layer of Zn-Al Layered Double Hydroxide - Yasin, Yamin; Mushirah Ismail, Nur; Ahmad, Faujan (Asian Journal of Chemistry, 2013)
A drug-inorganic nanostructure material involving a pharmaceutically active compound lawsone intercalated Zn-Al layered double hydroxide (Law-LDHs) with Zn/Al = 4 has been assembled by the co-precipitation method. The deintercalation or the release of lawsone was found to be rapid initially followed by a more sustained release thereafter and this behaviour was found to be dependent on the pH of the release medium. The release kinetic of lawsone from the layer of layered double hydroxide was found to be governed by the first order kinetic. The release profile data and the results from the kinetic study indicate that the dissolution mechanism is mainly contributed to the release behaviour of lawsone from the layer of layered double hydroxides. It is suggested that the layered double hydroxides may have an application as the basis of a drug delivery medium.